2012
DOI: 10.1016/j.jtcvs.2012.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo rehabilitation of non–heart-beating donor lungs in preclinical porcine model: Delayed perfusion results in superior lung function

Abstract: Objectives Ex vivo lung perfusion (EVLP) is a promising modality for the evaluation and treatment of marginal donor lungs. The optimal timing of EVLP initiation and potential for rehabilitation of donor lungs with extended warm-ischemic times is unknown. This study compares the efficacy of different treatment strategies for uncontrolled non-heart-beating donor lungs. Methods Mature swine underwent hypoxic arrest followed by 60 minutes of no-touch warm-ischemia. Lungs were harvested and flushed with 4°C Perfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
71
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 24 publications
13
71
1
1
Order By: Relevance
“…Firstly, the refinement of donor selection was illustrated by the study of Sanchez et al, which showed that, despite similar clinical characteristics and alveolocapillary barrier properties after the period of cardiac arrest and warm ischemia, donor lungs that did not receive prearrest heparinization had significantly worse physiological performance on EVLP compared to lungs from donors that received pre-arrest heparin (32). Secondly, the normothermic and metabolically active environment restored by EVLP provides an ideal platform for therapeutic manipulation of the DCDD organ (33)(34)(35)(36). EVLP-treated lungs showed better posttransplant lung function and less microthrombi formation compared to no-EVLP lungs in a DCDD experimental study (37).…”
Section: Dcdd-no Evlp Vs Dcdd þ Evlpmentioning
confidence: 99%
“…Firstly, the refinement of donor selection was illustrated by the study of Sanchez et al, which showed that, despite similar clinical characteristics and alveolocapillary barrier properties after the period of cardiac arrest and warm ischemia, donor lungs that did not receive prearrest heparinization had significantly worse physiological performance on EVLP compared to lungs from donors that received pre-arrest heparin (32). Secondly, the normothermic and metabolically active environment restored by EVLP provides an ideal platform for therapeutic manipulation of the DCDD organ (33)(34)(35)(36). EVLP-treated lungs showed better posttransplant lung function and less microthrombi formation compared to no-EVLP lungs in a DCDD experimental study (37).…”
Section: Dcdd-no Evlp Vs Dcdd þ Evlpmentioning
confidence: 99%
“…4 You follow the PICOT format, which serves as the starting point for identification of important key words used in the search process: 5 • Population: heart transplant patients • Intervention: heart transplantation with ex-vivo perfusion • Comparison: heart transplantation with cold storage • Outcome: patient survival and graft survival • Time horizon: 30 days after transplant You then conduct a literature search in PubMed Clinical Queries using the search terms "heart transplantation" AND "ex-vivo perfusion" AND "cold storage," using the "Therapy" and "Broad" filters. You identify 10 articles: 7 ex-vivo human/animal studies, [6][7][8][9][10][11][12] 1 nonrandomized clinical study, 13 1 review 14 and 1 RCT. 15 The RCT addresses your research question and has the benefit of being level-I evidence.…”
Section: Finding the Evidencementioning
confidence: 99%
“…Our group and others have demonstrated in preclinical models that DCD lungs with extended warm ischemic times (up to 60 minutes) may be rehabilitated by EVLP to an acceptable state for transplantation [106,120]. These results have been furthered by clinical studies in which initially rejected human donor lungs have been rehabilitated to acceptable standards for transplantation [121,122].…”
Section: Discussionmentioning
confidence: 84%
“…Steen solution within the circuit was gradually warmed from 4°C to 37°C through the circuit water bath, and EVLP continued for 60 minutes. Steen solution perfusate was supplemented with 10,000 IU heparin, 500mg cefazolin and 500mg methylprednisolone per 1500mL, modeling preclinical and clinical EVLP protocols [103,105]. Steen solution was also supplemented with vehicle (DMSO) for the EVLP group or with ATL1223 (30nM) for the ATL1223-treated group.…”
Section: Murine Evlpmentioning
confidence: 99%
See 1 more Smart Citation